Inhibitory Effect of Dodonaea viscosa var. angustifolia on the Virulence Properties of the Oral Pathogens Streptococcus mutans and Porphyromonas gingivalis. (7th October 2013) - Patel, Mrudula; Naidoo, Roxanne; Owotade, Foluso John
Abstract : Aim. This study investigated the effect of Dodonaea viscosa var. angustifolia (DVA) on the virulence properties of cariogenic Streptococcus mutans and Porphyromonas gingivalis implicated in periodontal diseases. Methods. S. mutans was cultured in tryptone broth containing a crude leaf extract of DVA for 16 hours, and the pH was measured after 10, 12, 14, and 16 h. Biofilms of S. mutans were grown on glass slides for 48 hours and exposed to plant extract for 30 minutes; the adherent cells were reincubated and the pH was measured at various time intervals. Minimum bactericidal concentration of the extracts against the four periodontal pathogens was determined. The effect of the subinhibitory concentration of plant extract on the production of proteinases by P. gingivalis was also evaluated. Results. DVA had no effect on acid production by S. mutans biofilms; however, it significantly inhibited acid production in planktonic cells. Periodontal pathogens were completely eliminated at low concentrations ranging from 0.09 to 0.02 mg/mL of crude plant extracts. At subinhibitory concentrations, DVA significantly reduced Arg-gingipain (24%) and Lys-gingipain (53%) production by P. gingivalis (P ≤ 0.01 ). Conclusions. These results suggest that DVA has the potential to be used to control oral infections including dental caries and periodontal diseases.